This can't be that Short!

Algebra Level 4

k = 1 m [ ( k 2 + 1 ) k ! ] = 1999 × 2000 ! \displaystyle \sum_{k=1}^m \left [ (k^2 + 1) \ k! \right ] = 1999 \times 2000!

What value of m m satisfies the above summation?


The answer is 1999.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

First we prove i = a b i i ! = ( b + 1 ) ! a ! \sum_{i=a}^b i*i! = (b+1)! - a!

Proof:- i = a b i i ! \sum_{i=a}^b i*i!

= i = a b ( i + 1 ) i ! i ! = \sum_{i=a}^b (i+1)*i! - i!

= i = a b ( i + 1 ) ! i ! = \sum_{i=a}^b (i+1)! - i!

= ( a + 1 ) ! a ! + ( a + 2 ) ! ( a + 1 ) ! + + ( b + 1 ) ! b ! = (a+1)! - a! + (a+2)! - (a+1)! + \dots + (b+1)! - b!

= ( b + 1 ) ! a ! = (b+1)! - a! .

Now to the question.

k = 1 m ( k 2 + 1 ) k ! \sum_{k=1}^m (k^2 + 1)k!

= k = 1 m ( k 2 + 2 k + 1 ) k ! 2 k k ! =\sum_{k=1}^m (k^2 +2k+ 1)k! - 2k*k!

= k = 1 m ( k + 1 ) 2 k ! 2 k = 1 m k k ! =\sum_{k=1}^m (k+1)^2k! - 2\sum_{k=1}^m k*k!

= k = 1 m ( k + 1 ) ( k + 1 ) ! 2 ( ( m + 1 ) ! 1 ! ) = \sum_{k=1}^m (k+1)*(k+1)! - 2((m+1)! - 1!)

Putting l = k + 1 l = k+1 , l = 2 l =2 when k = 1 k = 1 and l = m + 1 l = m+1 when k = m k = m .

= l = 0 m + 1 l l ! 2 ( m + 1 ) ! + 2 = \sum_{l=0}^{m+1}l*l! - 2(m+1)! + 2

= ( m + 2 ) ! 2 ! 2 ( m + 1 ) ! + 2 = (m+2)! - 2! - 2(m+1)! + 2

= ( m + 1 ) ! ( m + 2 2 ) = (m+1)!(m+2 - 2)

= m ( m + 1 ) ! = m*(m+1)!

Comparing with 1999 ( 2000 ) ! 1999*(2000)! , we see that m = 1999 m = \boxed{1999}

Nicely done ! :)

Keshav Tiwari - 6 years, 5 months ago
Sujoy Roy
Dec 19, 2014

We know r r ! = [ ( r + 1 ) r ] r ! = ( r + 1 ) ! r ! r*r! = [(r+1)-r]r!= (r+1)!-r! .

So, ( k 2 + 1 ) k ! = k ( k k ! ) + k ! (k^2+1)k!= k(k*k!)+k!

= k [ ( k + 1 ) ! k ! ] + k ! =k[(k+1)!-k!]+k!

= [ ( k + 2 ) 2 ] ( k + 1 ) ! k k ! + k ! =[(k+2)-2](k+1)!-k*k!+k!

= ( k + 2 ) ! 2 ( k + 1 ) ! ( k + 1 ) ! + 2 k ! =(k+2)!-2(k+1)!-(k+1)!+2k!

= [ ( k + 2 ) ! ( k + 1 ) ! ] 2 [ ( k + 1 ) ! k ! ] =[(k+2)!-(k+1)!]-2[(k+1)!-k!]

Now, k = 1 m [ ( k 2 + 1 ) k ! ] \sum^m_{k=1}[(k^2+1)k!]

= k = 1 m [ ( k + 2 ) ! ( k + 1 ) ! ] 2 k = 1 m [ ( k + 1 ) ! k ! ] = \sum^m_{k=1}[(k+2)!-(k+1)!]- 2\sum^m_{k=1}[(k+1)!-k!]

= ( m + 2 ) ! 2 ! 2 [ ( m + 1 ) ! 1 ] =(m+2)!-2!-2[(m+1)!-1] = ( m + 1 ) ! [ m + 2 1 ] = m ( m + 1 ) ! = 1999 ( 2000 ) ! = (m+1)![m+2-1]=m*(m+1)!=1999*(2000)!

So, m = 1999 m=\boxed{1999} .

On the first line:r r!=[(r+1)-1] r!

Lucas Toledo - 4 years, 3 months ago
Ayush Verma
Jan 19, 2015

( k 2 + 1 ) k ! = { ( k + 2 ) ( k + 1 ) 3 ( k + 1 ) + 2 } k ! = ( k + 2 ) ! 3 ( k + 1 ) ! + 2 k ! = { ( k + 2 ) ! ( k + 1 ) ! } 2 { ( k + 1 ) ! k ! } t e l e s c o p i n g . . . k = 1 m ( k 2 + 1 ) k ! = { ( m + 2 ) ! 2 ! } 2 { ( m + 1 ) ! 1 ! } = { ( m + 2 ) ! 2 ( m + 1 ) ! } { 2 ! 2.1 ! } = m ( m + 1 ) ! = 1999 × 2000 ! m = 1999 \left( { k }^{ 2 }+1 \right) k!=\left\{ \left( k+2 \right) \left( k+1 \right) -3\left( k+1 \right) +2 \right\} k!\\ \\ \quad =\left( k+2 \right) !-3\left( k+1 \right) !+2k!\\ \\ \quad =\left\{ \left( k+2 \right) !-\left( k+1 \right) ! \right\} -2\left\{ \left( k+1 \right) !-k! \right\} \\ \\ telescoping...\\ \\ \sum _{ k=1 }^{ m }{ \left( { k }^{ 2 }+1 \right) k!=\left\{ \left( m+2 \right) !-2! \right\} -2\left\{ \left( m+1 \right) !-1! \right\} } \\ \\ =\left\{ \left( m+2 \right) !-2\left( m+1 \right) ! \right\} -\left\{ 2!-2.1! \right\} \\ \\ =m\left( m+1 \right) !=1999\times 2000!\\ \\ \Rightarrow m=1999

nice solution thnxx

Sayandeep Ghosh - 4 years, 7 months ago

Note: The following solution is hinted by an online friend FAlin from Taiwan's forum telnet://ptt.cc or https://www.ptt.cc/bbs/Math/

Note that ( k 2 + 1 ) k ! = ( k 2 + k k + 1 ) k ! = [ k ( k + 1 ) ( k 1 ) ] k ! = k ( k + 1 ) ! ( k 1 ) k ! (k^2+1)k! = (k^2+k-k+1)k! = [k(k+1)-(k-1)]k! = k(k+1)!-(k-1)k! then

k = 1 m [ ( k 2 + 1 ) k ! ] = k = 1 m [ k ( k + 1 ) ! ( k 1 ) k ! ] = k = 1 m [ ( k 1 ) k ! + k ( k + 1 ) ! ] \sum_{k=1}^m [(k^2+1)k!] = \sum_{k=1}^m [k(k+1)!-(k-1)k!] = \sum_{k=1}^m [-(k-1)k!+k(k+1)!]

= [ 0 1 ! + 1 2 ! ] + [ 1 2 ! + 2 3 ! ] + [ 2 3 ! + 3 4 ! ] + [ 3 4 ! + 4 5 ! ] + [ 4 5 ! + 5 6 ! ] + . . . = [-0*1!+1*2!]+[-1*2!+2*3!]+[-2*3!+3*4!]+[-3*4!+4*5!]+[-4*5!+5*6!]+... (telescoping)

+ [ ( m 1 ) m ! + m ( m + 1 ) ! ] = m ( m + 1 ) ! +[-(m-1)m!+m(m+1)!] = m(m+1)!

Therefore, 1999*2000! = k = 1 1999 [ ( k 2 + 1 ) k ! ] \sum_{k=1}^{1999} [(k^2+1)k!] , m=1999

Prakriti Bansal
Feb 7, 2015

follow up question: is your observation correct?

sounds interesting, though a simple mathematical induction would suffice..

Eric Jan Escober - 4 years, 6 months ago
Paola Ramírez
Jan 19, 2015

( k 2 + 1 ) ( k ! ) (k^{2}+1)(k!) is: For k 1 = ( 1 + 1 ) ( 1 ! ) = 2 k_1=(1+1)(1!)=2

For k 2 = ( 4 + 1 ) ( 2 ! ) = 10 k_2=(4+1)(2!)=10

For k 3 = ( 9 + 1 ) ( 3 ! ) = 60 k_3=(9+1)(3!)=60

For k 4 = ( 16 + 1 ) ( 4 ! ) = 408 k_4=(16+1)(4!)=408

For k 5 = ( 25 + 1 ) ( 5 ! ) = 3120 k_5=(25+1)(5!)=3120

Let S k i = k = 1 k i [ ( k 2 + 1 ) ( k ! ) ] Sk_i=\sum\limits_{k=1}^{k_i}[(k^2+1)(k!)]

S k 1 = 2 2 ! × 1 Sk_1=2 \Rightarrow 2!\times1

S k 2 = 12 3 ! × 2 Sk_2=12 \Rightarrow 3!\times2

S k 3 = 72 4 ! × 3 Sk_3=72 \Rightarrow 4!\times3

S k 4 = 480 5 ! × 4 Sk_4=480 \Rightarrow 5!\times4

By induction proof that: k = 1 m = ( m ) ( m + 1 ) ! \sum\limits_{k=1}^{m}=(m)(m+1)!

Step 1 k = 1 1 [ ( k 2 + 1 ) ( k ! ) ] = ( 1 ) ( 1 + 1 ) ! = 2 \sum\limits_{k=1}^{1}[(k^2+1)(k!)]=(1)(1+1)!=2 k 1 = ( 1 + 1 ) ( 1 ! ) = 2 k_1=(1+1)(1!)=2

Step 2 k = 1 m = ( m ) ( m + 1 ) ! \sum\limits_{k=1}^{m}=(m)(m+1)! is true.

Step 3 Proof that k = 1 m + 1 = ( m + 1 ) ( m + 2 ) ! \sum\limits_{k=1}^{m+1}=(m+1)(m+2)! k = 1 m + 1 [ ( k 2 + 1 ) ( k ! ) ] = ( m ) ( m + 1 ) ! + ( ( m + 1 ) 2 + 1 ) ( m + 1 ) ! \sum\limits_{k=1}^{m+1}[(k^2+1)(k!)]=(m)(m+1)!+((m+1)^2+1)(m+1)! k = 1 m + 1 [ ( k 2 + 1 ) ( k ! ) ] = ( m ) ( m + 1 ) ! + ( ( m 2 + 2 m + 1 + 1 ) ( m + 1 ) ! \sum\limits_{k=1}^{m+1}[(k^2+1)(k!)]=(m)(m+1)!+((m^2+2m+1+1)(m+1)! k = 1 m + 1 [ ( k 2 + 1 ) ( k ! ) ] = ( m + 1 ) ! ( m 2 + 3 m + 2 ) \sum\limits_{k=1}^{m+1}[(k^2+1)(k!)]=(m+1)!(m^2+3m+2) k = 1 m + 1 [ ( k 2 + 1 ) ( k ! ) ] = ( m + 1 ) ! ( m + 2 ) ( m + 1 ) \sum\limits_{k=1}^{m+1}[(k^2+1)(k!)]=(m+1)!(m+2)(m+1) k = 1 m + 1 [ ( k 2 + 1 ) ( k ! ) ] = ( m + 2 ) ! ( m + 1 ) \sum\limits_{k=1}^{m+1}[(k^2+1)(k!)]=(m+2)!(m+1)\blacksquare

For S k i = k = 1 m [ ( k 2 + 1 ) ( k ! ) = 1999 × 2000 ! Sk_i=\sum\limits_{k=1}^{m}[(k^2+1)(k!)=1999\times 2000! m = 1999 \boxed{m=1999}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...